2020
DOI: 10.1016/j.plefa.2020.102175
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-CoA synthetases as regulators of brain phospholipid acyl-chain diversity

Abstract: Each individual cell-type is defined by its distinct morphology, phenotype, molecular and lipidomic profile. The importance of maintaining cell-specific lipidomic profiles is exemplified by the numerous diseases, disorders, and dysfunctional outcomes that occur as a direct result of altered lipidome. Therefore, the mechanisms regulating cellular lipidome diversity play a role in maintaining essential biological functions. The brain is an organ particularly rich in phospholipids, the main constituents of cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 194 publications
0
20
0
Order By: Relevance
“…A number of results in the literature indicate that astrocytes express ACSL6 (20,(24)(25)(26)(27)(28). To directly test the role of astrocytic ACSL6, we generated astrocyte-specific ACSL6-deficient mice using the glial fibrillary acidic protein (GFAP) promoter Cre driver (Acsl6 G-/-) (17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of results in the literature indicate that astrocytes express ACSL6 (20,(24)(25)(26)(27)(28). To directly test the role of astrocytic ACSL6, we generated astrocyte-specific ACSL6-deficient mice using the glial fibrillary acidic protein (GFAP) promoter Cre driver (Acsl6 G-/-) (17).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ACSL6 deficiency does not cause a DHA deficit in glial cells, arguably the major cell type driving lipid mediator metabolism, thereby potentially limiting the impact of ACSL6 on lipid mediator homeostasis. Because ACSL6 expression is identified as astrocyte enriched in numerous databases (20,(24)(25)(26)(27)(28), we were surprised that the loss of ACSL6 in astrocytes had minimal impact on brain membrane lipid composition. However, these databases use cells derived from animals early in development, failing to capture transcripts, such as Acsl6, that present in latestage mature neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the fact that the brain is the fattiest organ after adipose tissue, ACSL4 is regarded as an important enzyme for neurodegenerative diseases due to its role in lipid metabolism although it has not been fully investigated in AD (25). An in vitro study of embryonic stem cells showed that the nerve growth factor, retinoic acid induced neuronal differentiation, and neurite growth were weakened by a knockout of the ACSL4 gene (26).…”
Section: Discussionmentioning
confidence: 99%
“…Rat monoclonal antibodies were raised against lipid peroxidation-modified ApoE by incubating ApoE monomers with Cu-oxidized 1-palmitoyl-2-arachidonoyl-sn-phosphatidylcholine (PAPC), a phospholipid that it is particularly enriched in hippocampus. 52 Two clones (15E8 [PxPAPC-ApoEa], and 2B7 [PxPAPC-ApoEb])…”
Section: Apoer2-apoe Complexes and Aldehyde-crosslinked Apoe Multimersmentioning
confidence: 99%